PHYSICAL EXERCISE FOR THE TREATMENT OF TYPE 2 DIABETES - CASE STUDY - Veronica Balteanu (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2016)
The study highlights the contribution of physical exercises/ activities within a complex treatment for type 2 diabetes, a disease with high incidence and serious and irreversible complications. The study includes theoretical notions, specific therapeutic conduct - medication, diet, and kinesiotherapy, applied within individualized treatment. Material and method. Functional parameters (constant lab works, glycaemia) and specialized clinical evaluations reflect the effect of the treatment applied to the patient over a 6-month period within a study case. Findings and discussions. As concluded by findings, the effects of the medication and diet prescribed by the specialist physician were enhanced by physical activity (an important factor in the favourable evolution of treatment for type 2 diabetes, reflected in the initial and final evaluations of the study). Conclusions: treatment alterations, corrections, or additions are necessary in terms of content and necessity of exercising systematically for the rest of the patient's life. An individualized workout routine adapted to the person suffering from type 2 diabetes was found to have beneficial effects upon the functional parameters impaired by this condition.